Ängste in Zeiten von COVID-19 und anderen Gesundheitskrisen - Bendau, A. (Nervenarzt, 2020)
BACKGROUND: Epidemics and pandemics and the measures taken to contain their spread are accompanied by numerous stressors, which can lead in particular to severe anxiety. OBJECTIVE: This article describes the components and determinants of these anxiety symptoms, potential resilience and risk factors and appropriate recommendations for action. METHODS: The article presents an overview of research results regarding COVID-19 and previous epidemics and pandemics (e.g., HIV, SARS, MERS, Ebola and swine flu). Furthermore, official recommendations for action are presented. RESULTS: Anxiety symptoms frequently occur in epidemics and pandemics, especially in the early phase and usually decrease in the further course. Although other aspects of different infectious diseases vary, the associated fears are similar and include e.g. the fear of health-related, social and economic consequences. Resilience and risk factors in various epidemics and pandemics are comparable. Self-efficacy expectation, tolerance of uncertainty, normalization, routines, safety and social support usually have a protective effect. In contrast, excessive media consumption, female gender, work in a medical context, suppression, pre-existing diseases, unhealthy behavior and closer exposure to the virus are often accompanied by more severe anxiety. CONCLUSION: Fears should be observed and addressed in order to reduce pathological processes, especially in vulnerable groups. It is advisable to promote resilience factors and to counteract risk factors with preventive and therapeutic measures. For this purpose, the development and empirical testing of specific interventions as well as further longitudinal studies are needed.